2023
DOI: 10.3322/caac.21818
|View full text |Cite
|
Sign up to set email alerts
|

Immunosurveillance in clinical cancer management

Guido Kroemer,
Timothy A. Chan,
Alexander M. M. Eggermont
et al.

Abstract: The progression of cancer involves a critical step in which malignant cells escape from control by the immune system. Antineoplastic agents are particularly efficient when they succeed in restoring such control (immunosurveillance) or at least establish an equilibrium state that slows down disease progression. This is true not only for immunotherapies, such as immune checkpoint inhibitors (ICIs), but also for conventional chemotherapy, targeted anticancer agents, and radiation therapy. Thus, therapeutics that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 260 publications
0
12
0
Order By: Relevance
“…Cancer immunotherapy, a treatment method that leverages the immune system to combat cancer, represents a potential therapeutic option. 37 However, a significant portion of GBM patients fail to respond to such treatment. 38 The diminished response observed can be ascribed to the immunosuppressive properties of GBM, which impair the ability of the innate immune system to eradicate tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer immunotherapy, a treatment method that leverages the immune system to combat cancer, represents a potential therapeutic option. 37 However, a significant portion of GBM patients fail to respond to such treatment. 38 The diminished response observed can be ascribed to the immunosuppressive properties of GBM, which impair the ability of the innate immune system to eradicate tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer immunotherapy, a treatment method that leverages the immune system to combat cancer, represents a potential therapeutic option . However, a significant portion of GBM patients fail to respond to such treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Although long-realized, tumor immunology can actually be regarded as an emerging field [ 187 ]. During the past two decades, immune system has been increasingly recognized as an important player in control or contribute to development of cancer [ 188 , 189 ]. Initially hypothesized by Schreiber et al, it has now been widely accepted that cancer immunoediting, a process consisting of three sequential phases termed elimination, equilibrium, and escape, involves in cancer evolution [ 190 ].…”
Section: Tumor Biology Of Exosomesmentioning
confidence: 99%
“… Lu et al (2021) synthesized an activator (NBS-1MT) with a small molecule inhibitor and photosensitizer and found that it can induce oxidative stress to generate considerable ICD via pyroptosis in breast cancer cells. Although preclinical studies have laid a certain theoretical foundation, the clinical transformation of the combination of targeted therapy and ICIs is still not optimistic ( Kroemer et al, 2023 ).…”
Section: Icd Inducers and Molecular Mechanismmentioning
confidence: 99%